Listening to motivational music while walking elicits more positive affective response in patients with cystic fibrosis. (May 2016) - Calik-Kutukcu, Ebru; Saglam, Melda; Vardar-Yagli, Naciye; Cakmak, Aslihan; Inal-Ince, Deniz; Bozdemir-Ozel, Cemile; Sonbahar-Ulu, Hazal; Arikan, Hulya; Yalcin, Ebru; Karakaya, Jale
Abstract: Objective: The purpose of this study was to investigate the effects of motivational and relaxation music on affective responses during exercise in patients with cystic fibrosis (CF). Methods: Thirty-seven patients with CF performed the 6-min walk test (6MWT) under three experimental conditions: listening to no music, relaxation music, and motivational music. 6-min distance × body weight product (6MWORK) was calculated for each trial. Patients' affective responses during exercise was evaluated with Feeling Scale (FS). The motivational qualities of music were evaluated with the Brunel Music Rating Inventory-2 (BMRI-2). Results: 6MWORK was significantly lower while listening to relaxation music compared to 6MWORK without music (p < 0.05). FS and BMRI-2 scores were significantly higher during 6MWT with motivational music than 6MWT with relaxation music (p < 0.05). Conclusions: Carefully selected motivational music can lead to positive affective response during exercise and increase the enjoyment of patients from exercises in CF. Highlights: Motivational music while walking creates a more positive affective response in CF. Metabolic demands of walking are lower by listening to relaxation music. Motivational or relaxation music results in similar rate of perceived exertion.